Universal ТPC-installation with thermoelectric converters - Mazurenko, Alexander; Roman, Tatiana; Burova, Zinaida; Dekusha, Leonid (My University, 2012)
The article provides a description of the created ТФХ - installation with thermoelectric converters, given their technical and metrological characteristics, possibilities of application. Was used standard, according to DSTU, measuring transducers.
Keywords: thermoelectric converters; термоелектричні перетворювачі; термоэлектрические преобразователи; thermal characteristics; coefficients of thermal conductivity and thermal resistance; теплові характеристики; коефіцієнти теплопровідності і термічного опору; тепловые характеристики; коэффициенты теплопроводности и термического сопротивления; кафедра електропостачання і енергоменеджменту; кафедра технології ресторанної і аюрведичної продукції